E-Government Transformation Towards E-Governance in Public Service Processes at the Population and Civil Registration Office of Gresik Regency - Baharuddin Kasim; Dian Ferriswara; Enny Haryati; Sri Kamariyah (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the Transformation of E-Government Towards E-Governance in the Public Service Process at the Population and Civil Registration Office of Gresik Regency. The utilization of information technology in public services is one of the government’s efforts to improve administrative efficiency, transparency, and the quality of services provided to the public.This research employs a qualitative approach with a descriptive method to provide an in-depth depiction of the implementation of E-Governance in population administration services. Data collection techniques include interviews, observations, and documentation, while data analysis follows the stages of Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing alternative interpretations, and Forming and/or refining generalizable theory from the case study.The results indicate that the implementation of the Transformation of E-Government Towards E-Governance in the Public Service Process at the Population and Civil Registration Office of Gresik Regency is carried out through several key dimensions, namely E-Administration, E-Service, and E-Society. The E-Administration dimension is reflected in the use of digital-based administrative systems for managing population data and processing document applications electronically. The E-Service dimension shows that online services provide easier access for the public to manage population documents more quickly and efficiently. Meanwhile, the E-Society dimension demonstrates an increased utilization of information technology by the public in accessing population administration services. Nevertheless, the implementation of digital services still faces several challenges, such as limited digital literacy among the public and uneven internet access. This study concludes that the application of E-Governance in population administration services in Gresik Regency has made a positive contribution to improving the quality of public services through the utilization of information technology.